Perspective Taking: Building a neurocognitive framework for integrating the "social" and the "spatial" - Klaus Kessler (Frontiers Research Topics, 2015)
Background: Interacting with other people involves spatial awareness of one's own body and the other's body and viewpoint. In the past, social cognition has focused largely on belief reasoning, which is abstracted away from spatial and bodily representations, while there is a strong tradition of work on spatial and object representation which does not consider social interactions. These two domains have flourished independently. A small but growing body of research examines how awareness of space and body relates to the ability to interpret and interact with others. This also builds on the growing awareness that many cognitive processes are embodied, which could be of relevance for the integration of the social and spatial domains: Online mental transformations of spatial representations have been shown to rely on simulated body movements and various aspects of social interaction have been related to the simulation of a conspecific's behaviour within the observer's bodily repertoire. Both dimensions of embodied transformations or mappings seem to serve the purpose of establishing alignment between the observer and a target. In spatial cognition research the target is spatially defined as a particular viewpoint or frame of reference (FOR), yet, in social interaction research another viewpoint is occupied by another's mind, which crucially requires perspective taking in the sense of considering what another person experiences from a different viewpoint. Perspective taking has been studied in different ways within developmental psychology, cognitive psychology, psycholinguistics, neuropsychology and cognitive neuroscience over the last few decades, yet, integrative approaches for channelling all information into a unified account of perspective taking and viewpoint transformations have not been presented so far. Aims: This Research Topic aims to bring together the social and the spatial, and to highlight findings and methods which can unify research across areas. In particular, the topic aims to advance our current theories and set the stage for future developments of the field by clarifying and linking theoretical concepts across disciplines. Scope: The focus of this Research Topic is on the SPATIAL and the SOCIAL, and we anticipate that all submissions will touch on both aspects and will explicitly attempt to bridge conceptual gaps. Social questions could include questions of how people judge another person's viewpoint or spatial capacities, or how they imagine themselves from different points of view. Spatial questions could include consideration of different physical configurations of the body and the arrangement of different viewpoints, including mental rotation of objects or viewpoints that have social relevance. Questions could also relate to how individual differences (in personality, sex, development, culture, species etc.) influence or determine social and spatial perspective judgements. Many different methods can be used to explore perspective taking, including mental chronometry, behavioural tasks, EEG/MEG and fMRI, child development, neuropsychological patients, virtual reality and more. Bringing together results and approaches from these different domains is a key aim of this Research Topic. We welcome submissions of experimental papers, reviews and theory papers which cover these topics.